Detection of Endangered Aquatic Plants in Rapid Streams Using Environmental DNA - Tsukamoto, Yuta; Yonezawa, Satoru; Katayama, Natsu; Isagi, Yuji (Frontiers in Ecology and Evolution, 2021)
Podostemaceae are a eudicot family of plants that grow on rapid streams and waterfalls. Two genera and six species of this family are distributed in Japan, all of which are threatened with extinction. It is difficult to find these species from the river side and it takes much effort to investigate their distribution. In this study, we attempted to determine the presence and absence of the Podostemaceae species by environmental DNA (eDNA) metabarcoding. Four species of Podostemaceae were detected near four known habitats, and the detected species were in perfect agreement with the results of a past survey that was based on visual observation. The marker used in this study had sufficient resolution to distinguish all six Podostemaceae species distributed in Japan and detected multiple species growing in a site. These results show that eDNA metabarcoding can quickly detect rare aquatic plants that are difficult to find by visual observation and can provide important information regarding their conservation.